Diet quality measured by four a priori-defined diet quality indices is associated with lipid-soluble micronutrients in the Multiethnic Cohort Study (MEC) - Aumueller, N.; Boushey, Carol; Franke, A.; Cooney, R.; Monroe, K.; Haiman, C.; Wilkens, L.; Kolonel, L.; Le Marchand, L.; Maskarinec, G. (Nature Publishing Group, 2018)
© 2018, Springer Nature Limited. Background/Objectives: This study examined the long-term relation of lipid-soluble micronutrients with diet quality as assessed by four a priori-defined dietary patterns. Subjects/Methods: In a prospective design, nutritional biomarkers (carotenoids, tocopherols, retinol, and coenzyme Q10) were measured using a validated HPLC-based assay. General linear models were applied to obtain covariate-adjusted means of biomarkers for tertiles of four a priori diet quality indices: Healthy Eating Index (HEI) 2010, Alternative HEI (AHEI) 2010, Alternate Mediterranean Diet Score (aMED), and Dietary Approaches to Stop Hypertension (DASH). For a subcohort of 8367 participants within the Multiethnic Cohort (MEC), diet was assessed by a validated quantitative food frequency questionnaire in 1993–96 and serum was collected in 2001–06. Results: Participants with the highest diet-quality scores had significantly higher serum concentrations of all carotenoids, total tocopherols, and a-tocopherol, whereas ?-tocopherol was inversely associated with diet quality. Adjusted means for the lowest vs. highest tertile of HEI 2010 were 1.2 vs. 1.5 mg/L for total carotenoids, 11.4 vs. 12.3 mg/L for total tocopherols, and 1.9 vs. 1.6 mg/L for ?-tocopherol (ptrend < 0.0001). The associations for the other dietary indices were similar; no indication for sex and ethnic differences was detected. Vegetable and fruit components were major predictors of most circulating micronutrients, but most other components were also associated. Conclusions: Higher diet-quality scores measured by four a priori diet quality indices were significantly associated higher serum concentrations of carotenoids and a-tocopherol, whereas ?-tocopherol was inversely associated with diet quality.